Regio-isomerism directed electrocatalysis for energy efficient zinc-air battery - Mukhopadhyay, Sanchayita; Devendrachari, Mruthyunjayachari Chattanahalli; Kanade, Sandeep C.; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Thotiyl, Musthafa Ottakam (iScience, 2022)
We have investigated the role of ligand isomerism in modulating the mechanisms and kinetics associated with charge/ discharge chemistry of an aqueous metal-air battery. The dominant electron-withdrawing inductive effect (-I effect) and the diminished electron-withdrawing resonance effect (-R effect) in the alpha-NO2 isomer noticeably diminishes the rate of oxygen reduction (ORR) and oxygen evolution reactions (OER) on the catalytic Co-center. In their beta-counterpart, the cumulative -I and -R effects noticeably enhance the OER and ORR kinetics on the same catalytic Co-center. Therefore, the regioisomerism of the -NO2 functionality amplifies the kinetics of ORR/OER without influencing their mechanistic pathways. When isomeric electrocatalysts are integrated to aid the charge chemistry of a Zn-air battery, the overpotential could be decreased by similar to 250mV with beta-NO2 isomer leading to a round-trip efficiency as high as 60%. This work contributes to the design of novel molecular platforms to target the overall round-trip efficiency of energy storage and conversion devices.

Unusual ligand assistance in molecular electrocatalysis via interfacial proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Chame, Pallavi Vyankuram; Ghosh, Prasenjit; Vinod, Chathakudath Prabhakaran; Makri Nimbegondi Kotresh, Harish; Kanade, Sandeep C.; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2023)
We show that the ability of the ligand to reorganizethe electricdouble layer (EDL) often dominates the electrocatalysis contrary totheir inductive effect in the spectrochemical series, leading to counterintuitiveelectrocatalysis. With water oxidation and chlorine evolution as theprobe reactions, the same catalytic entity with carboxy functionalizedligand exhibited surprisingly higher electrochemical activity in comparisonto the aggressively electron-withdrawing nitro functionalized ligands,which is contrary to their actual location in the spectrochemicalseries. Spectroscopic and electrochemical analyses suggest the enrichmentof catalytically active species in the carboxy substituted ligandvia proton charge assembly in the EDL that in turn enhances the kineticsof the overall electrochemical process. This demonstration of lessobvious ligands becoming indispensable in electrocatalysis suggestsa blind designing of ligands solely based on their inductive effectshould be reconsidered as it will prevent the utilization of the maximumpotential of the molecule in electrocatalysis.

Electrochemical energy storage in an organic supercapacitor via a non-electrochemical proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Devendrachari, Mruthyunjayachari Chattanahalli; Mendhe, Rahul Mahadeo; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Chemical Science, 2024)
Contrary to conventional beliefs, we show how a functional ligand that does not exhibit any redox activity elevates the charge storage capability of an electric double layer via a proton charge assembly. Compared to an unsubstituted ligand, a non-redox active carboxy ligand demonstrated nearly a 4-fold increase in charge storage, impressive capacitive retention even at a rate of 900C, and approximately a 2-fold decrease in leakage currents with an enhancement in energy density up to approximately 70% via a non-electrochemical route of proton charge assembly. Generalizability of these findings is presented with various non-redox active functional units that can undergo proton charge assembly in the ligand. This demonstration of non-redox active functional units enriching supercapacitive charge storage via proton charge assembly contributes to the rational design of ligands for energy storage applications.

Switchable molecular electrocatalysis - Dutt, Shifali; Kottaichamy, Alagar Raja; Dargily, Neethu Christudas; Mukhopadhyay, Sanchayita; Nayak, Bhojkumar; Devendrachari, Mruthyunjayachari Chattanhali; Vinod, Chatakudhath Prabakaran; Kotresh, Harish Makri Nimbegondi; Thotiyl, Musthafa Ottakam (CHEMICAL SCIENCE, 2024)
Keywords: CO2 reduction; COBALT PHTHALOCYANINE; NANOPOROUS GOLD; oxygen reduction

Synergistic effects of the substrate-ligand interaction in metal-organic complexes on the de-electronation kinetics of a vitamin C fuel cell - Parmar, Muskan; Mukhopadhyay, Sanchayita; Mondal, Ritwik; Nayak, Bhojkumar; Dargily, Neethu Christudas; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Ottakam Thotiyl, Musthafa (Dalton Transactions, 2024)
The rising demand for portable energy conversion devices has spurred the advancement of direct liquid fuel cells (DLFCs) employing fuels such as alcohol, ammonia, hydrazine, and vitamin C. In these devices, various precious metal platforms have been explored to increase the de-electronation kinetics and reduce catalyst poisoning, but with substantial cost implications. We demonstrate the crucial role of ligands in non-precious organometallic complexes in influencing the de-electronation kinetics of fuel molecules through a unique substrate-ligand synergistic interaction. This unique chemistry imparts electron deficiency at the catalytic metal center while simultaneously populating the ligand with an extensive proton charge assembly. This distinct substrate-ligand interaction enhances the DLFC performance by coulombically dragging the substrate with a distinct amplification in its de-electronation kinetics. By integrating this approach with a ferricyanide/ferrocyanide half-cell reaction, a precious metal-free vitamin C fuel cell is developed, which is capable of generating an open circuit voltage of similar to 950 mV, a peak power density of similar to 97 mW cm-2 at a peak current density of similar to 215 mA cm-2 with the performance metrics nearly 1.7 times higher than a precious metal based DLFC. This highlights the potential of the substrate-ligand synergy in the design of efficient molecular catalysts for energy conversion applications. A precious metal-free biomass fuel cell through substrate-ligand interactions.